Nomenclature of renal involvement in diabetes mellitus: unify to manage diversity - Marques, María; Portolés, José; Mora-Fernández, Carmen; Ortiz, Alberto; Navarro-González, Juan F. (Frontiers in Medicine, 2025)
Diabetes mellitus is the most common cause of chronic kidney disease leading to kidney failure and premature death. Over the years, the nomenclature of kidney involvement in diabetes mellitus has evolved, driven both by the understanding that the phenotype may be more diverse than initially thought and by pragmatism. In clinical practice, most patients with diabetes mellitus do not undergo a comprehensive work-up (including kidney biopsy and genetic testing) to exclude the presence or coexistence of additional factors or other kidney diseases. Furthermore, the inclusion criteria for successful kidney protection clinical trials that are the basis of current guidelines covered a wide range of kidney phenotypes under the label of “diabetes and kidney disease,” without requiring proactive efforts to exclude other nephropathies. The aim of this review is to provide a critical review of the most common chronic kidney disease phenotypes in the context of diabetes mellitus and discuss the evolving nomenclature. Various topics are discuss diabetic kidney disease, classic diabetic nephropathy, regression of albuminuria, rapid progression, non-albuminuric and non-proteinuric kidney disease, the connections between and the impact of aging on these phenotypes and a glimpse into future phenotypes resulting from proactive prevention rather than reactive treatment of kidney disease in diabetes.